1999
DOI: 10.1034/j.1399-3003.1999.14a17.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiol regulation of the production of TNF-α, IL-6 and IL-8 by human alveolar macrophages

Abstract: Reactive oxygen intermediates exert signalling functions and modulate gene transcription, particularly for pro-inflammatory cytokines. Since exogenous as well as endogenous thiols could be potent inhibitors of the production of cytokines, the effects of N-acetylcysteine (NAC), glutathione (GSH) and modulated GSH synthesis on the production of tumour necrosis factor (TNF)-a, interleukin (IL)-6 and IL-8 by human alveolar macrophages (AMs) was evaluated, as well as the potential role of intracellular GSH depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
54
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 35 publications
4
54
2
1
Order By: Relevance
“…Accordingly, the present authors decided to stimulate AM immediately after sorting and to quantify the concentration of the different inflammatory mediators both early (4 h) and late (24 h). Fifthly, the concentration of LPS used and the time points chosen were similar to those of previous studies [10,41,42]. However, different results in LTB 4 and/or ROI release may have been found if different LPS concentrations and/or different time points had been used [17,41].…”
Section: Discussionmentioning
confidence: 49%
“…Accordingly, the present authors decided to stimulate AM immediately after sorting and to quantify the concentration of the different inflammatory mediators both early (4 h) and late (24 h). Fifthly, the concentration of LPS used and the time points chosen were similar to those of previous studies [10,41,42]. However, different results in LTB 4 and/or ROI release may have been found if different LPS concentrations and/or different time points had been used [17,41].…”
Section: Discussionmentioning
confidence: 49%
“…Many previous studies have indicated that the intracellular GSH level modifies cytokine production in monocytes and macrophages [11,22]. As shown in Table 2, co-administration resulted in a Th1-dominant pattern compared with the control and single-administration groups, and this was found to become a Th2-dominant pattern by 24 hr.…”
Section: Discussionmentioning
confidence: 73%
“…It should also be noted that the association between GSH and cytokine response has biological plausibility. GSH is part of the thiol regulation pathway within all human (9,12,13). Depleting immune cells of GSH modulates their ability to produce cytokines to a variety of foreign antigens (9,12,13).…”
mentioning
confidence: 99%
“…GSH is part of the thiol regulation pathway within all human (9,12,13). Depleting immune cells of GSH modulates their ability to produce cytokines to a variety of foreign antigens (9,12,13). Our finding that human GSH depletion is associated with decreased cytokine release from PBMCs in response to V. vulnificus may be a first step in understanding the human cellular mechanisms behind susceptibility to this bacterium.…”
mentioning
confidence: 99%